THE ANALYSIS OF DRUG RELATED PROBLEMS (DRPS) IN PATIENTS WITH THE CASE OF CHRONIC KIDNEY DISEASE (CKD) INPATIENT ROOM OF BHAYANGKARA SARTIKA ASIH TK II HOSPITAL BANDUNG CITY - Setiadi, Anggi
Chronic kidney disease (CKD) is a progressive degenerative function of the kidneys (deteriorating neural functions) occurring over months or years. Complex medical problems are commonly found in patients diagnosed with CKD whether or not accompanied with comorbidity which leads to drug-related problems affecting the therapy. This study is aimed to identify and to analyze the case of potential drug-related problems in patients with CKD. This research was descriptive stud using cross-sectional method with the data obtained from patient’s medical record from May 2022 until July 2022. A total sampling technique was used to gain 76 patients as subjects. The subject’s criteria included being recently hospitalized and diagnosed with CKD (with or without comorbidity), over 18 years (male/ female), having GFR<60 mL min/ 1,73. Drug Related Problems (DRP’s) were classified according to Pharmaceutical Care Network Europe (PCNE) version 9.1. The analysis result of potential DRP’s showed that there were 4 cases untreated indications (5,26%), 70 cases of potential drug interaction (93,33%), and 67 cases of polypharmacy (88,16%). According to bivariate analysis, it showed that disease and numbers of drugs significantly increase the case of DRP’s in patients (p < 0.05). Multivariate analysis using logistic regression showed that the numbers of drugs (p < 0.05, OR: 2.618)), the numbers of disease diagnosis has significant differences in increasing cases of DRP’s in patients , as well as the OR results for the variable disease diagnosis, namely 2.382, meaning patients with CKD disease those who get multi-diagnosis have a 2 times the risk of the occurrence of DRPs.